Two new species and records of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae) from southeastern China - Shavrin, Alexey V. (Zootaxa, 2014)
Two new species of the genus Lesteva Latreille, 1792 are described from southeastern China: L. (s. str.) hajeki sp. n. from Jiangxi province (Jinggang Shan Mts.) and L. (inc. sed.) ruzickai sp. n. from Guangdong province (Nanling Mts.). L. (s. str.) elegantula Rougemont, 2000 and L. (s. str.) flavopunctata Rougemont, 2000 are recorded for Jiangxi province for the first time.